Evaluating SARS-CoV-2 Seroconversion Following Relieve of Confinement Measures - Gonçalves, Juliana; Sousa, Rita L.; Jacinto, Maria J.; Silva, Daniela A.; Paula, Filipe; Sousa, Rute; Zahedi, Sara; Carvalho, Joana; Cabral, M. Guadalupe; Costa, Manuela; Branco, Jaime C.; Canhão, Helena; et al. (Frontiers in Medicine, 2020)
Seroprevalence studies are crucial both for estimating the prevalence of SARS-CoV-2 exposure and to provide a measure for the efficiency of the confinement measures. Portuguese universities were closed on March 16th 2020, when Portugal only registered 62 SARS-CoV-2 infection cases per million. We have validated a SARS-CoV-2 ELISA assay to a stabilized full-length spike protein using 216 pre-pandemic and 19 molecularly diagnosed COVID-19 patients’ samples. At NOVA University of Lisbon, presential work was partially resumed on May 25th with staggered schedules. From June 15th to 30th, three to four weeks after the easing of confinement measures, we screened 1636 collaborators of NOVA university of Lisbon for the presence of SARS-CoV-2 spike specific IgA and IgG antibodies. We found that spike-specific IgG in 50 of 1636 participants (3.0%) none of which had anti-spike IgA antibodies. As participants self-reported as asymptomatic or paucisymptomatic, our study also provides a measurement of the prevalence of asymptomatic/paucysymptomatic SARS-CoV-2 infections. Additional serological surveys in different population subgroups will paint a broader picture of the effect of the confinement measures in the broader community.